Studying neural selectivity for motion using high-field fMRI - Beckett, Alexander (2013)
Functional magnetic resonance imaging (fMRI) offers a number of opportunities to non-invasively study the properties of the human visual system. Advances in scanner technology, particularly the development of high-field scanners, allow improvements in fMRI such as higher resolution and higher signal to noise ratio (SNR). We aimed to examine what these advances in scanner technology, combined with novel analysis techniques, can tell us about the processing of motion stimuli in the human visual cortex.